A Portrait of the Level of Legal Awareness of Crime Victims Regarding the Right to Restitution (Study in Talun District, Blitar Regency, 2024) - Wibowo, Anton (Proceedings of International Conference of Graduate School on Sustainability, 2026)
The right to restitution for victims of crime is a right that must be fulfilled as mandated in Article 136 paragraph (1) of Law No. 1 of 2023 concerning the Criminal Code, which states, "victims have the right to obtain restitution from perpetrators of criminal acts or third parties in accordance with the provisions of statutory regulations." However, problems arise when victims lack the right to restitution for the losses they suffer, as occurred in the Blitar District Court's Decision Number 313/Pid.B/2023/PN Blt. Therefore, it is essential to assess crime victims' legal awareness of their right to restitution. This research was conducted in Blitar Regency, specifically in Talun District, due to the high number of crimes reported there as of 2024. The method used in this research is empirical, collecting data from crime victims and law enforcement through interviews about their awareness of their right to restitution. The research results regarding awareness of the right to restitution for crime victims in Talun District, Blitar Regency, are relatively low. The primary factor contributing to the victims' limited understanding is the lack of education and information they receive about their right to restitution. Based on this conclusion, the author recommends that law enforcement agencies conduct extensive outreach to the public about the right to restitution, especially victims of crime, to ensure their rights are fulfilled and to build a more just legal society.